Sosialisasi Pemilu 2019 Untuk Pemilih Pemula Kota Depok - Khikmatul Islah; Juardi Juardi; Eman Sulaeman Nasim (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
The year 2019 was the year of the people's party in Indonesia, where every Indonesian citizen got their right to deliver their aspiration through the general election which would be held on April 17, 2019. This general election would be held simultaneously to elect the president and vice president and also the council members. Slightly different from the previous general election which had separated agenda between the president and vice president and the council members. The role of General Election Commission (KPU) in the general election was as an organizer that very important in succeeding the general election. As the organizer, KPU also had a big role in encouraging people to actively participate in casting their votes. One of the ways carried out by KPU Depok in order to encourage the voters of the Depok city to cast their votes was by conducting socialization. In the 2019 general election, one of the targets of the socialization conducted by KPU Depok was the first-time voters. Of the total number of 2,466 first-time voters registered as the Final Voters List (DPT), KPU Depok was targeting 100% of the first-time voters to participate in the April 17, 2019 general election. Various ways were made by KPU Depok to socialize and educate first-time voters all about the election. One of them was to collaborate with STIAMI Institute in order to socialize the 2019 general election for the first-time voters in Depok. The specific target to be achieved in the community service was to encourage the first-time voters to come to the polling stations (TPS) to cast their voting rights in the 2019 general election, also educate them the proper way to cast their votes in the 2019 general election. The method used in this community service was by socializing and conducting interview about the 2019 general election.